1986
DOI: 10.1007/bf00870279
|View full text |Cite
|
Sign up to set email alerts
|

Muscle enzyme activity and insulin sensitivity in Type 1 (insulin-dependent) diabetes mellitus

Abstract: Summary.The mechanisms of insulin insensitivity in diabetes are poorly understood. We have therefore assessed the relationship between glucose disposal during a euglycaemic clamp, muscle glycogen formation, and the activities of insulin regulated enzymes within skeletal muscle in five Type I (insulin-dependent) diabetic patients, both on conventional injection therapy (HbA1 11.0-4-1.0 (SD) %) and after 6 weeks continuous subcutaneous insulin infusion (HbA1 7.6 + 1.4%, p < 0.01). On both regimens, overnight eug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
(38 reference statements)
2
17
0
Order By: Relevance
“…Furthermore, changes in serum insulin within the physiological range with a 2.8-fold increase over a 24-h period did not contribute to the acute regulation of total GS activity and GS mRNA and immunoreactive protein abundance in muscle but normalized the muscle GS activation in diabetic patients. Hence, the present data suggest that the impaired glycogen synthesis of skeletal muscle from Type 1 diabetic patients in poor metabolic control [1][2][3] is caused by post-translational modifications of the GS enzyme which may be secondary to metabolic derangements [3,7]. This interpretation of results is compatible with the study of Vuorinen-Markkola et al [28] demonstrating that 24 h of hyperglycaemia induces a severe impairment of whole-body non-oxidative glucose metabolism in Type I diabetic patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, changes in serum insulin within the physiological range with a 2.8-fold increase over a 24-h period did not contribute to the acute regulation of total GS activity and GS mRNA and immunoreactive protein abundance in muscle but normalized the muscle GS activation in diabetic patients. Hence, the present data suggest that the impaired glycogen synthesis of skeletal muscle from Type 1 diabetic patients in poor metabolic control [1][2][3] is caused by post-translational modifications of the GS enzyme which may be secondary to metabolic derangements [3,7]. This interpretation of results is compatible with the study of Vuorinen-Markkola et al [28] demonstrating that 24 h of hyperglycaemia induces a severe impairment of whole-body non-oxidative glucose metabolism in Type I diabetic patients.…”
Section: Discussionsupporting
confidence: 82%
“…The two forms of the enzyme are interconverted by phosphorylation-dephosphorytation reactions with G6P allosterically activating the phosphorylated form of GS, whereas insulin acts covalently on GS by reducing and increasing the activities of specific kinases and phosphatases, respectively [12]. The decreased glucose clearance of peripheral tissues in Type i diabetic patients has been shown to be accompanied by decreased glycogen synthase activity in skeletal muscle [1,10]. Phosphofructokinase (PFK) is a rate-limiting enzyme in glycolysis [13] catalysing the transformation of fructose 6-phosphate to fructose-l,6-diphosphate, a process which is allosterically regulated by several metabolites [13] and previous studies in diabetic rodents have shown an impairment of muscle PFK activity [14].…”
mentioning
confidence: 99%
“…However, PDHa did not differ between groups. The only previous study to examine muscle PDHa in pa- tients with type 1 diabetes also reported no difference at rest compared with control subjects (14). Thus, although speculative, it is possible that our type 1 diabetic group had lower muscle lactate transport during intense exercise than the control group.…”
Section: Muscle Enzyme Activitymentioning
confidence: 58%
“…Muscle glycogen synthase is also less activated by insulin in type I diabetic human subjects, in whom total glycogen synthase activity is not reduced (26). To our knowledge, however, human glycogen synthase phospha- tase has only been measured in PMN (27,28 (14,17) in animal experiments.…”
Section: Discussionmentioning
confidence: 95%